Heart rate variability in newborn foals and its association with illness: a pilot study. Issue 1 (1st January 2021) - Vitale, Valentina; Conte, Giuseppe; Baragli, Paolo; Jose-Cunilleras, Eduard; Sgorbini, Micaela
Abstract: This study aimed to investigate differences in heart rate variability (HRV) between healthy and sick neonatal foals with a variety of diagnosis and to verify whether some HRV parameters could be associated with sepsis and/or survival. Twenty-one foals were included in the study: nine were healthy and 12 were sick. Retrospectively, sick foals were divided into sub-groups (non-septic vs. septic and non-survivor vs. survivor) for statistical analysis. Heart rate was recorded daily for 20 min and a 5-min period was used for heart rate variability analysis. Data on HRV variables were analysed using a linear model. Least-square means with their standard errors were reported, and treatment effects were declared significant at p  < .05. To isolate the group that differed from the others, Tukey's test was used as a multiple comparison procedure. Pearson's correlations between variables were calculated, to estimate their relationship. Standard Deviation of the RR intervals and Standard Deviation 2 by the Poincaré plot was significantly lower in sick foals compared with healthy subjects, but there were no differences between survivors and non-survivors. Healthy foals presented a significantly lower Sample Entropy and heart rate compared with sick foals. HRV analysis is a non-invasive, rapid, and economical measurement tool that can be added to other parameters to improve the accuracy of predicting in-hospital mortality in foals. Further studies should be conducted with a larger sample of foals to confirm these findings and to evaluate the clinical usefulness of HRV analysis during neonatal diseases. Highlights: This study investigated differences in heart rate variability (HRV) between sick and healthy neonatal foals Standard Deviation of the RR intervals was significantly lower in sick compared with healthy foals, but there were no differences between survivors and non-survivors. HRV analysis is a non-invasive, rapid, and economical tool that can be added to other parameters to improve the accuracy of predicting mortality in foals.